The Metabolic Pathways of Yeast and Acetic Acid Bacteria During Fruit Vinegar Fermentation and Their Influence on Flavor Development - Yinggang Ge; Yifei Wu; Aihemaitijiang Aihaiti; Liang Wang; Yu Wang; Jun Xing; Min Zhu; Jingyang Hong (Microorganisms)
Fruit vinegar is a beverage derived from fruits or fruit processing by-products through microbial fermentation. This vinegar possesses a distinctive flavor profile and contains bioactive compounds. It is typically produced using liquid fermentation technology. As consumer demand for the flavor quality of fruit vinegar has increased, precise control over flavor compounds has become crucial for enhancing the quality of fermentation products. Vinegar contains numerous characteristic flavor compounds, including esters, aldehydes, alcohols, and organic acids. These unique flavors primarily result from the accumulation of flavor compounds generated by different raw materials and microorganisms during fermentation. Specifically, yeast and acetobacter promote the formation of distinct fruit vinegar flavors by facilitating the breakdown of carbohydrates, amino acids, and proteins in fruits, as well as the redox and esterification reactions involving alcohols. This paper reviews the metabolic pathways of yeast and acetic acid bacteria during fruit vinegar fermentation and discusses key volatile compounds that influence the flavor of fruit vinegar and their potential relationships, providing theoretical support for regulating flavor quality.